Analisis Kinerja Struktur Crane Monorel 8 Ton Menggunakan Analisis Rangka dan Evaluasi Sambungan Baut - Ari Handoko; Yopan Rahmad Aldori; Mislan Mislan; Fadhli Farsa; Nova Arief Setyanto; Masrajuddin Masrajuddin (CV. IRA PUBLISHING, 2025)
This study analyzes the structural performance of an 8-ton monorail crane using frame analysis simulation in Autodesk Inventor Professional 2012. The structure is made of ASTM A36 carbon steel, and the applied load is calculated with a safety factor of 1.67, yielding a load of 131,061.6 N. The evaluated parameters include bending moment, shear force, normal stress, and displacement. The results show a maximum bending moment of 1,538,000 N·mm, a maximum shear force of 97,063 N, and a maximum stress of 151.6 MPa, which is below the allowable stress of 250 MPa. The maximum displacement of 29.95 mm is also lower than the allowable limit of 30.5 mm according to SNI 03-1729-2002. In addition, bolt-connection evaluation confirms safe performance under loading. Therefore, the monorail crane structure is considered safe and suitable for lifting 8 tons.